2023
DOI: 10.1371/journal.pone.0283712
|View full text |Cite
|
Sign up to set email alerts
|

Wide and deep learning based approaches for classification of Alzheimer’s disease using genome-wide association studies

Abstract: The increasing incidence of Alzheimer’s disease (AD) has been leading towards a significant growth in socioeconomic challenges. A reliable prediction of AD might be useful to mitigate or at-least slow down its progression for which, identification of the factors affecting the AD and its accurate diagnoses, are vital. In this study, we use Genome-Wide Association Studies (GWAS) dataset which comprises significant genetic markers of complex diseases. The original dataset contains large number of attributes (6209… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…For performance purposes, the genotyping data utilized in this study comprises the top 121 markers reported in a previous 2023 study 61 . Exact feature list can be found in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For performance purposes, the genotyping data utilized in this study comprises the top 121 markers reported in a previous 2023 study 61 . Exact feature list can be found in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, “bed” files provide machine codes that are unintelligible to humans. These codes are composed of 8-bit codes that map the data between fam and bim files and represent the genotype codes 61 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research in Alzheimer's disease [69] used a hybrid feature selection approach based on association test, principal component analysis and the Boruta algorithm, to identify the most promising predictors. The selected features are then forwarded to wide and deep neural network models to classify the Alzheimer's disease cases and healthy controls.…”
Section: Machine Learning Application Areas In Gwasmentioning
confidence: 99%
“…The best-known longitudinal population-based biobanks include the UK Biobank [98], the China Kadoorie Biobank [99], the Estonian Biobank [100], and the Lifelines Biobank [101]. The use of this data through the implementation of AI methods has allowed high-throughput analysis and has led to new discoveries in the medical field [69] and shown to improve prediction in comparison to an unimodal approach [94].…”
Section: Multimodal Omics Databasesmentioning
confidence: 99%